Biofortified rice variety Fedearroz BioZN-035 for Colombia - CGIAR Research Program on Rice (2021)
This variety was developed with harvestplus, CIAT, CIRAD . The final selection was done with the next users, small farmers in the region of Bolivar in Colombia. The farmers select the type of grain and cooking quality, as well as the adaptation to the different growing environments